NORMUROD NORQOBILOV HIKOYALARIDA BOLA RUHIYATI VA TABIAT TALQINI - Bozozrov, Sobirjon (Журнал иностранных языков и лингвистики, 2021)
This article deals with the problems of the child's psyche and the interpretation of nature in the stories of the writer Normurad Norkobilov "Butterfly", "The Land of the Sunless".